Euro-Mediterranean relations after the Arab spring persistence in times of change - Horst, Jakob; Jünemann, Annette, 1959-; Rothe, Delf. (Farnham : Ashgate Publishing Ltd, 2013)
The 'Arab Spring' triggered paradigmatic shifts but, despite these changes, much in the Euro-Mediterranean region remains the same. Utilising 'Logics of Action', an innovative theoretical framework designed to capture the complexity of political interaction in one of the fastest changing regions in the world, this book discusses developments in the region before and after the Arab Spring that can be characterised by a continuation of the norm. Offering a completely new perspective on the events of the 'Arab Spring' it identifies something that seems paradoxical at first sight; persistence in t.
Logics of action in the Euro-Mediterranean political space : an introduction to the analytical framework / Jakob Horst, Annette Jünemann, Florian Kühn, Eva Maggi and Delf Rothe -- Change to stay the same : the European Union and the logics of institutional reform in Morocco / Eva-Maria Maggi -- Facing a dilemma : the EU's promotion of gender-democracy after the "Arab Spring" / Annette Jünemann -- Learning to cope : the development of European immigration policies concerning the Mediterranean caught between national and supra-national narratives / Peter Seeberg -- Free trade, development and authoritarianism in a rentier economy : intentions and reality of the EU's logic of action in Algeria / Jakob Horst -- A revolution in the logics of action? : renegotiating the authoritarian social contract in Egypt / Cilja Harders -- Blocked middle classes as an engine of change in the Arab world? / Rachid Ouaissa -- Exploring the logics of moderate Islamists' political actions in the light of the "Arab Spring" : the cases of Jordan and Morocco / Kerstin Fritzsche and Ivesa Lübben -- On logics of the Egyptian transformation process and change / Ingrid El Masry -- Welcome to the desert : regional integration and identity change through an EU-MENA energy partnership? / Delf Rothe -- Mediterranean players par excellence? : sketching foreign-educated Syrians' logics of action / Tina Zintl -- Conclusion / Jakob Horst, Annette Jünemann, Delf Rothe.
Print version record.
Includes bibliographical references and index.
Keywords: European Union countries -- Foreign relations -- Arab countries; Arab countries -- Foreign relations -- European Union countries; European Union countries -- Foreign relations -- Mediterranean Region; Mediterranean Region -- Foreign relations -- European Union countries; Arab Spring, 2010-; Arab countries -- Politics and government -- 21st century; Mediterranean Region -- Politics and government -- 21st century; Arab countries -- Foreign relations -- European Union countries; Arab countries -- Politics and government -- 21st century; Arab Spring, 2010-; European Union countries -- Foreign relations -- Arab countries; European Union countries -- Foreign relations -- Mediterranean Region; Mediterranean Region -- Foreign relations -- European Union countries; Mediterranean Region -- Politics and government -- 21st century; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Politics and government; Arab countries; Europe -- European Union countries; Mediterranean Region; 2000 - 2099; Electronic books; Electronic books